Auditoría al rubro ingresos y cuentas por cobrar de una empresa que se dedica a importación y comercialización de electrodomésticos y productos varíos en la ciudad de Guayaquil por el año terminado el 31 de diciembre de 2007. - Amores Rodríguez, Priscila (2009)
This is a financial audit to an import and export electrical domestic and another items enterprise located in Guayaquil for the 2007 period closed at December 31. For an easy comprehension we divided in four parts as follows: Theoretical Framework, Planning the Audit, Implementation of audit tests and finally Conclusions and recommendations. Firstly, it provides a concrete theory that allows a clear understanding the financial activity in order to deliver to the earns an inform about the situation of the company and so can determine if the financial inform has been prepared accords with the regulation of the Generally Accepted Accounting Principles. In the next part we realize a real audit in fact to obtain an opinion about the financial statements in order to determine if this statement represent in a reasonable form the complete situation of the company, accord with NIA, NEC and GAAP. Through the test we can emit our recommendations.